Individual behavioral correlates of tail biting in pre-finishing piglets - Bagaria, Marc; Kuiper, Laura; Meijer, Ellen; Sterck, Elisabeth H. M. (Frontiers in Veterinary Science, 2022)
Introduction Tail biting is a widespread problem in pig production systems and has a negative impact on both animal welfare and farm income. This explorative study aims to validate how tail biting is related to general behaviors at the individual level and explore whether these behaviors are related to a particular type of tail biting: two-stage, sudden-forceful, obsessive, or epidemic. Methods This research was conducted in a standard commercial setting where 89 tail-docked pre-finishing piglets divided into 8 groups were observed 4 days per week from 5 to 8 weeks of age. Each piglet was observed for a total of 160 min using continuous focal sampling. Ten individual behaviors were recorded based on the general behaviors expected to be linked to giving tail biting (PCA1), receiving tail biting (PCA2), and tail biting damage (PCA3). These PCAs were assembled and related to tail biting given, tail biting received, and tail biting lesions. Results Tail biting did not lead to major damage on the piglets' tail at 8 weeks of age but was observed 420 times, where most of the individuals (72%) were categorized as “biters and victims.” When relating PCA1 with tail biting given, piglets that gave more tail biting showed more “active exploration.” When relating PCA2 with tail biting received, piglets receiving more tail biting were more “explored while active” and “attacked and explored.” When relating PCA2 with tail biting lesions, piglets presenting lesions showed more “agonism.” Surprisingly, tail biting lesions were not significantly related to PCA3. The relationship between explorative behaviors and tail biting indicates that the pre-damage stage of two-stage tail biting was the predominant tail biting type, while the damaging stage was likely incipient. The relationship between tail biting and aggression, as well as the minor tail lesions observed suggest that sudden-forceful tail biting was probably present even though it was rarely seen. Obsessive and epidemic tail biting were not observed. Discussion This study demonstrates that studying tail biting at the individual level helps to identify the type of tail biting present. This gives directions to farmers for applying appropriate measures to prevent the development of tail biting behavior in piglets.